Transformasi Budaya Konsumsi Mahasiswa di Era Cashless Society: Studi Fenomenologi Penggunaan E-Wallet di Universitas Jember - Diva Nabilla; Alifiyah Jihan Fadilah; Salma Nur Azizha; Naufal Desta Putra Ismail (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The development of digital technology has driven the emergence of a cashless society era that transforms how people transact, including among university students. The use of e-wallets such as GoPay, Dana, ShopeePay, and SeaBank is increasingly widespread on campuses, yet in-depth studies on their impact on student consumption culture from a cultural sociology perspective remain limited. This study aims to describe the transformation of student consumption culture at the University of Jember through e-wallet usage in the cashless society era. A qualitative phenomenological method was employed, with data collected through in-depth interviews with 8 informants from various faculties and semesters selected via purposive sampling, supplemented by observation and documentation. Data analysis followed the Miles & Huberman interactive model. The results reveal three main findings: (1) e-wallets have altered student consumption patterns through increased transaction frequency and the emergence of new expenditure categories, particularly food delivery and online shopping; (2) e-wallets have transformed in meaning from a mere transaction tool to a marker of social identity and modernity; and (3) the socio-cultural impacts include changes in group payment dynamics, reinforcement of consumerist behavior through promo and cashback features, and a decline in students’ financial awareness. This study concludes that the transformation of student consumption culture in the cashless society era coincides with the formation of a new digital habitus that shapes social relations on campus.